Morphological and Redox/Glycative Alterations in the PCOS Oviducts: Modulating Effects of Carnitines in PCOS Mice - Mariacarla De Rubeis; Ilaria Antenisca Mascitti; Domenica Cocciolone; Martina Placidi; Teresa Vergara; Giovanna Di Emidio; Guido Macchiarelli; Carla Tatone; Stefania Annarita Nottola; Maria Grazia Palmerini (Biology)
Polycystic ovarian syndrome (PCOS) is a heterogeneous condition characterized by hyperandrogenism (HA), polycystic ovaries, and dysfunctional ovulation, and it is associated with metabolic problems such as insulin resistance (IR) and obesity. After having investigated the morphological and antioxidant/antiglycative alterations on mouse ovaries and uteri, we here focus on PCOS oviducts, a tract of the reproductive system essential for the nourishment and transport of gametes and embryos. The modulating effects of L-carnitine (LC) and acetyl-L-carnitine (ALC) were also assessed. CD1 mice were administered or not with dehydroepiandrosterone (DHEA, 6 mg/100 g body weight) for 20 days, alone or with 0.40 mg of L-carnitine (LC) and 0.20 mg of acetyl-L-carnitine (ALC). Oviducts were then subjected to histology and immunohistochemistry to evaluate their morphology and collagen deposition, and steroidogenesis. Oxidative, mitochondrial, and methylglyoxal (MG)-dependent damage was also investigated. Transmission electron microscopy was used to detect ultrastructural alterations. The PCOS oviducts were affected by hyperfibrosis, hyperplasia, hypertrophy, and altered steroidogenesis, with oxidative alterations associated with MethylGlyoxal-Advanced Glycation End product (MG-AGE) accumulation. A reduced ciliary coverage and numerous dilated intercellular spaces were found in the epithelium. LC-ALC administration mitigated PCOS oviductal alterations. These results provide evidence for the detrimental action of oxidative and glycative stress in PCOS oviducts, confirming a protective role of carnitines on the PCOS phenotype.